Mediastinal tuberculosis following descending necrotizing mediastinitis: A case report. Issue 6 (1st May 2022) - Matsumoto, Akira; Soma, Toshihiko; Shoji, Tsuyoshi; Katakura, Hiromichi
Abstract: Tuberculosis is a disease that causes latent infection and is sometimes activated by a variety of factors. Descending necrotizing mediastinitis (DNM) is a serious disease caused by spreading oropharyngeal infection. We present a case of mediastinal tuberculosis following mediastinal dissection and antibiotic therapy for DNM. A 62‐year‐old man was admitted to the hospital with an increasing mass in the right mediastinum during outpatient follow‐up after surgical drainage and antibiotic treatment for idiopathic cervical abscess and left DNM caused by oral bacteria. The patient underwent right mediastinal abscess dissection 4 months after the last surgery. As a result of culture tests, no general bacteria but Mycobacterium tuberculosis was detected. Anti‐tuberculosis treatment was continued for 9 months, and the patient has progressed without any recurrence of infection. The possibility of relapse of tuberculosis should always be considered in patients with unexplained masses. Abstract : Tuberculosis is a disease that causes latent infection and is sometimes activated by a variety of factors. Descending necrotizing mediastinitis (DNM) is a serious disease caused by spreading oropharyngeal infection. We present a case of mediastinal tuberculosis following mediastinal dissection and antibiotic therapy for DNM.